How to Teach Pre-Service Teachers to Make a Didactic Program? The Collaborative Learning Associated with Mobile Devices - Soler Costa, Rebeca; Mauri Medrano, Marta; Lafarga Ostáriz, Pablo; Moreno-Guerrero, Antonio-José (Sustainability, 2020)
Today, pedagogical proposals are increasingly moving away from purely traditional approaches, with a proliferation of active methodologies in the teaching–learning processes. This research aims to find out the effectiveness of the collaborative method in mobile learning, as opposed to traditional methodology, for university students in the learning of the didactic program. The research methodology is quantitative, applying a quasi-experimental design with a control group and experimental group. The results show that the collaborative learning teaching method associated with mobile learning mainly increases motivation, the relationships between teachers and students, the relationships between students and content, the relationships between students and students, autonomy in learning, pedagogical collaboration between students, problem-solving, and the sense of time in the training process. It is concluded that the collaborative learning method associated with mobile learning is more effective for learning didactic programming than the traditional method.